NeuroBridge: a prototype platform for discovery of the long-tail neuroimaging data - Wang, Lei; Ambite, José Luis; Appaji, Abhishek; Bijsterbosch, Janine; Dockes, Jerome; Herrick, Rick; Kogan, Alex; Lander, Howard; Marcus, Daniel; Moore, Stephen M.; Poline, Jean-Baptiste; Rajasekar, Arcot; et al. (Frontiers in Neuroinformatics, 2023)
Open science initiatives have enabled sharing of large amounts of already collected data.However, significant gaps remain regarding how to find appropriate data, including underutilized data that exist in the long tail of science. We demonstrate the NeuroBridge prototype and its ability to search PubMed Central full-text papers for information relevant to neuroimaging data collected from schizophrenia and addiction studies.The NeuroBridge architecture contained the following components: 1) Extensible ontology for modeling study metadata: subject population, imaging techniques, and relevant behavioral, cognitive, or clinical data. Details are described in the companion paper in this special issue; 2) A natural-language based document processor that leveraged pre-trained deep-learning models on a small-sample document corpus to establish efficient representations for each article as a collection of machine-recognized ontological terms; 3) Integrated search using ontology-driven similarity to query PubMed Central and NeuroQuery, which provides fMRI activation maps along with PubMed source articles.The NeuroBridge prototype contains a corpus of 356 papers from 2018 to 2021 describing schizophrenia and addiction neuroimaging studies, of which 186 were annotated with the NeuroBridge ontology. The search portal on the NeuroBridge website (https://neurobridges.org/) provides an interactive Query Builder, where the user builds queries by selecting NeuroBridge ontology terms to preserve the ontology tree structure. For each return entry, links to the PubMed abstract as well as to the PMC full-text article, if available, are presented. For each of the returned articles, we provided a list of clinical assessments described in the "Methods" section of the article. Articles returned from NeuroQuery based on the same search are also presented.The NeuroBridge prototype combined ontology-based search with natural-language text-mining approaches to demonstrate that papers relevant to a user's research question can be identified.The NeuroBridge prototype takes a first step towards identifying potential neuroimaging data described in full-text papers. Towards the overall goal of discovering "enough data of the right kind," ongoing work includes validating the document processor with a larger corpus, extending the ontology to include detailed imaging data, and extracting information regarding data availability from the returned publications to enhance data accessibility.